Saltwater encroachment investigation in deep multilayered coastal aquifers in North Kelantan - 347723 Wan Mokhtar Wan Nawang; Norhan Abd. Rahman; Seminar Penilaian Program IRPA & UPP Universiti Teknologi Malaysia (1992 : Universiti Teknologi Malaysia, Skudai, Malaysia)
07